Pengaruh Model Discovery Learning dan Kemandirian Belajar Terhadap Kemampuan Pemecahan Masalah Matematis pada Siswa SMK PGRI Dobo - Widia Beljeur; Ardianik Ardianik; Ahmad Hatip (Lembaga Riset dan Inovasi Almatani, 2023)
In learning mathematics, it is very important for students to have mathematical problem-solving skills, because problem-solving skills are an important aspect of mathematics that is needed for student success at various levels. By applying the right learning model and independent learning will be one of the factors that influence the ability to solve mathematical problems. The purpose of this study was to determine differences in mathematical problem solving abilities between learning independence (high, medium, low) and those who implement the Discovery Learning model and the Think Pair Share cooperative learning model and continue the influence of the interaction between the level of independent learning and the learning model. This study used a quantitative approach and this type of experimental research with a total sample of 63 students of class XI TKJ SMK PGRI Dobo. Data analysis in this study used the Two Way ANOVA test with a 3×2 factorial design. From the results of the study obtained 1) There is a very significant difference in the ability to solve mathematical problems between learning independence (high, medium, low) in class XI TKJ SMK PGRI Dobo students. 2) There is a very significant difference in the ability to solve mathematical problems between classes taught with the discovery learning model and the think pair share type cooperative learning model in class XI TKJ SMK PGRI Dobo. 3) There is an interaction effect between the level of independent learning with learning model on the ability to solve mathematical problems in class XI TKJ SMK PGRI Dobo students.